A computationally efficient scheme for feature extraction with kernel discriminant analysis. (February 2016) - Min, Hwang-Ki; Hou, Yuxi; Park, Sangwoo; Song, Iickho
Abstract: The kernel discriminant analysis (KDA), an extension of the linear discriminant analysis (LDA) and null space-based LDA into the kernel space, generally provides good pattern recognition (PR) performance for both small sample size (SSS) and non-SSS PR problems. Due to the eigen-decomposition technique adopted, however, the original scheme for the feature extraction with the KDA suffers from a high complexity burden. In this paper, we derive a transformation of the KDA into a linear equation problem, and propose a novel scheme for the feature extraction with the KDA. The proposed scheme is shown to provide us with a reduction of complexity without degradation of PR performance. In addition, to enhance the PR performance further, we address the incorporation of regularization into the proposed scheme. Abstract : Highlights: We propose a complexity-reduced scheme for the kernel discriminant analysis. The proposed scheme does not cause degradation of recognition accuracy performance. The core is the transformation of the original problem into a linear equation problem. We further address the incorporation of regularization into the proposed scheme.